2010
DOI: 10.1161/circulationaha.109.888297
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Simple Versus Complex Drug-Eluting Stenting for Bifurcation Lesions

Abstract: Background-The optimal strategy for treating coronary bifurcation lesions remains a subject of debate. With bare-metal stents, single-stent approaches appear to be superior to systematic 2-stent strategies. Drug-eluting stents, however, have low rates of restenosis and might offer improved outcomes with complex stenting techniques. Methods and Results-Patients with significant coronary bifurcation lesions were randomized to either a simple or complex stenting strategy with drug-eluting stents. In the simple st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(114 citation statements)
references
References 28 publications
4
109
1
Order By: Relevance
“…The immediate angiographic success was 100% in all patients in both groups, the procedural in-hospital success was 100% in all the patients in both groups, no documented ECG changes after intervention during the index hospitalization and no one from either group suffered in-hospital major complications. Results of our study were in agreement with that reported in the BBC trial [11]. Study.…”
Section: Meta-analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The immediate angiographic success was 100% in all patients in both groups, the procedural in-hospital success was 100% in all the patients in both groups, no documented ECG changes after intervention during the index hospitalization and no one from either group suffered in-hospital major complications. Results of our study were in agreement with that reported in the BBC trial [11]. Study.…”
Section: Meta-analysissupporting
confidence: 93%
“…The use of two stents minimizes lumen loss of one side during expansion of the other vessel [9]. Several studies [10][11][12] have concluded that stenting the main vessel (MV) with provisional stenting (PS) of side branches (SB) is preferable in the great majority of bifurcation lesions. Various techniques with the use of one or two stents have been developed to optimize the treatment of this subset of lesions [1][2][3][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, six randomised controlled trials (RCT) have compared the use of two stents versus a single-stent approach in the treatment of BL [15][16][17][18][19][20]. The BBC-ONE trial showed a clinical benefit favouring the single-stent technique, which was mainly driven by a reduction in periprocedural MI, of which clinical consequences are still a matter of debate [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of restenosis rate by introduction of DES led to the development of many techniques based on the implantation of two or more stents [17]. However, none of them was superior to MB stenting with the use of a single stent and provisional side-branch stenting [18][19][20][21]. Besides, despite significant progress in the stenting of bifurcation lesions multi-stent techniques are related to higher risk of periprocedural complications, mainly non-Q wave myo - cardial infarctions, not to mention the costs [19][20][21].…”
Section: Discussionmentioning
confidence: 99%